Studies on Some Enzyme Activities in Laminated and Germinal Layers of Hydatid Cysts Isolated From Different Intermediate Hosts in Zakho, Duhok Province, Kurdistan Region of Iraq. - Mero, Wijdan M.S.; AL Bosely, Araz R.I. (Science Journal of University of Zakho, 2014)
The current study deals with some enzyme activities in laminated and germinal layers of hydatid cysts isolated from liver and lungs of infected sheep, goats and cattle slaughtered in Zakho abattoirs and cysts isolated from humans. The activities of the enzymes, acid phosphatases (ACP), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), glutamate oxaloacetate transminase (GOT) and glutamate Pyruvate transaminase (GPT) were measured in cysts isolated from both liver and lungs of infected sheep, goats, cattle and humans. The activities of all of these enzymes were higher in laminated layer as compared with their activities in germinal layer, however in general infected host tissue showed the highest enzymatic activities as compared with hydatid cyst.